PERAN TOKOH AGAMA DALAM MEMUTUS RANTAI PERSEBARAN COVID-19 DI MEDIA ONLINE - Sholikha, Tiara Mar'atus (Jurnal Dakwah Tabligh, 2022)
Many figures have played an important role in overcoming the COVID-19 pandemic. This role is carried out by various parties, including religious leaders. Religious figures have charismatic figures and have special powers to influence the actions of the people who are in their community. messages conveyed by religious leaders also tend to be listened to and followed by people with similar beliefs. Therefore, this study aims to find out how the role of religious leaders in breaking the chain of the spread of COVID-19 in online media. To achieve this goal, this study uses a descriptive analysis method by taking research data from various media and articles that focus on the responses of religious leaders in breaking the Covid-19 chain in online media. This study concludes that the role of religious leaders in breaking the chain of the spread of COVID-19 is as a damper for public confusion, as a mouthpiece for pandemic information, and as role models.